2018
DOI: 10.1016/j.jval.2018.09.114
|View full text |Cite
|
Sign up to set email alerts
|

Pcn32 - The Effectiveness and Safety of Switching From Orginal Filgrastim to Biosimilar Filgrastim in Primary Prophylaxis of Chemotherapy Induced Febrile Neutropenia: A Retrospective Cohort Study

Abstract: products and its impact on access. METHODS: Volume, type and timelines of evidence generation was identified and compared between the four products. The scope of evidence includes early access programs (EAPs), expanded access programs, pivotal trial extension studies, and real world evidence. Time to positive health technology assessment (HTA) outcome was assessed in 4 major European markets. RESULTS: All products received CMA based on ongoing phase II or I/II trials and required phase III data for full MA, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In an oncology study, Al Rabayah et al (2018) also found an increase in both the frequency and duration of hospitalizations among patients who switched to a biosimilar in comparison to those who remained on the reference biologic (15.6% vs 12.6% and 7 days vs 6.4 days, respectively, follow-up period not specified) [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In an oncology study, Al Rabayah et al (2018) also found an increase in both the frequency and duration of hospitalizations among patients who switched to a biosimilar in comparison to those who remained on the reference biologic (15.6% vs 12.6% and 7 days vs 6.4 days, respectively, follow-up period not specified) [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…While these studies were scarce, they provided a better understanding of the savings or costs that were associated with the switch from the reference biologic to the biosimilar drug. Specifically, three studies reported on HCRU differences [6,33,34], three studies reported on cost differences [35][36][37], and one study reported on differences in both HCRU and overall costs [32]. With regards to HCRU, all studies concluded that NMS was associated with a significant or numerical increase in HCRU among patients who underwent originator-tobiosimilar NMS [6,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations